A case study of Malaysian rural secondary school students' attitudes towards learning English as a second language - Zulkefly Balan, Farah; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper proposes a study to understand rural secondary school students’ attitudes towards learning the English language, to explore what kinds of sociocultural and psychological factors that may contribute to the rural secondary school students attitudes towards learning the English language, to determine how these sociocultural and psychological factors may contribute to the rural secondary school students attitudes towards learning the English language, and to suggest ways to foster positive attitudes for rural secondary school students to learn the English language. From the literature review, the problem with students’ lack of English language proficiency is most prominent among rural students in Malaysia. Gardner and Lambert (1959), as cited in Ler (2012), stated that success in language learning is related to attitudinal variables. These variables are; i) attitudes towards the language learned and ii) the attitudes towards the language speakers as well as their culture. Language learning can be said as a complicated process as it involves internal and external factors (Wang, 2008). In this proposal, the researchers propose to study 10 students from a rural school in the southern state of the country as the main participants. These students will be interviewed twice and will be observed at least thrice during English lesson in the classrooms. The researchers will also analyze their learning materials (i.e. their notes, exercises and homework). To complement the data, the researchers also intend to interview 10 parents (of the students chosen), 3 English teachers from the school, and 3 prominent educational authorities (i.e., the school principal, the district’s SISC+ English teacher and the Head of Education District Office). Through this thorough exploration, the researchers hope to find out rural secondary school students’ attitudes; how do sociocultural and psychological factors affect their attitudes, and how to improve those attitudes.